THE REASONS FOR USING EMOJIS ON WHATSAPP CHATS: A CASE STUDY OF INDONESIAN STUDENTS’ TRANSLINGUAL PRACTICE - Murniati Murniati (Universitas Bunda Mulia, 2023)
Translingual practice recognizes language repertoire in which both linguistics and non-linguistics sources are put together in one’s brain and used when necessary (Canagarajah, 2013). Since one’s language repertoire is different from others, the language produced might also be different. The offline and online contexts might also differentiate the production of the language. In online communication, such as communication through WhatsApp, ones can interpret the linguistics and non-linguistic codes differently, including the emojis which are available in WhatsApp. Due to the different language repertoire, there must be reasons why emojis are used differently by WhatsApp users. This present study aims to find the reasons why emojis are used on WhatsApp chats which are written by students in academic contexts. The data is emojis used in WhatsApp chats used by five university students in a private university in Indonesia. Even though only five participants are joining this study, it aims to examine in-depth reasons why the emojis are used in WhatsApp chats. The data is gained by asking the participants to convert the WhatsApp chats to Word files. In addition, to know the detailed information about the interpretations of the use of emojis in WhatsApp, this study applied MIMI (The Mobile Instant Messaging Interview) (Kaufmann & Peil, 2020; Gibson, 2020; Enochsonn, 2011).It is analyzed by using Netnography (Kozinets, 2015). The results show that there are six reasons why the emojis are used on WhatsApp chats. It can be concluded that in Translingual Practice, language is not fixed; instead, the meaning emerges in the language contact zone.